Penerapan Media Augmented Reality dalam Meningkatkan Hasil Belajar Kearifan Lokal - Sapta, Mariam Nur Mutoharoh; Sapta, Andy (LPPM Universitas Terbuka, 2025)
Visual media has an important role in supporting the learning process of local wisdom. One form of media that can be applied to learning is Augmented Reality. This media offers an interesting interactive experience, so it has the potential to have a positive impact on its users. This study aims to analyze the application of Augmented Reality media in learning local wisdom in elementary schools and its effectiveness in improving students' understanding. This study uses a quantitative approach with an independent sample t-test analysis method and a pretest-posttest control group research design. The research subjects were students in two elementary schools in Pameungpeuk District, Bandung Regency. The results showed that the average posttest score of the experimental group reached 85.75, while the control group only obtained an average score of 55.04. Based on the hypothesis test, the result of t_count > t_table was obtained, so H₀ was rejected. Thus, there is a significant difference between the learning outcomes of the experimental and control groups. This study concludes that learning that utilizes Augmented Reality media is proven to be more effective than conventional learning methods.